World Citizenship
XXII, 234 p.
Keywords: This book discusses the various ways in which the security and prosperity of all countries in the world are linked - by military threats, environmental pollution, and social unrest created by poverty. It is argued that a process of education is needed to make people think in global terms, so that they develop an allegiance to humanity.